Ultrasonographic Diagnosis of Ileal Intussusception in Calf - Ribeiro, Ana Clara Sarzedas; Souto, Rodolfo José Cavalcanti; Silva, Tayrlla Polessa Rodrigues; Afonso, José Augusto Bastos; Mendonça, Carla Lopes; Costa, Nivaldo de Azevedo; Coutinho, Luiz Teles; Cajueiro, Jobson Filipe de Paula (Acta Scientiae Veterinariae, 2021)
Background: Intussusception, characterized by invagination of an intestinal segment into the lumen of the adjacent segment, is one of the main causes of intestinal obstruction in cattle, and occurs more frequently in calves. The diagnosis of the disease is based on the history, clinical examination, and complementary exams, which are a challenge in this species, especially in calves, in which transrectal palpation is limited. As it is a non-invasive, effective, and low-cost test, ultrasonography could be an important tool in the diagnosis of intestinal obstructions, in which time is essential for the prognosis. Therefore, the objective was to report a case of intussusception in a calf diagnosed by ultrasound. Case: A 4-month-old calf, weaned at 3 months and raised intensively, was treated at the Clínica de Bovinos de Garanhuns, campus of the Universidade Federal Rural de Pernambuco (CBG/UFRPE), with a history of apathy, anorexia, and dyschezia for 3 days. On physical examination, fever, moderate dehydration, tachycardia, tachypnea with polypnea, bilaterally bulging abdomen, sound of fluid on ballottement, ruminal and intestinal hypomotility, and melena were observed. The hematological findings revealed leukocytosis due to neutrophilia (degenerate neutrophils), hypoproteinemia, and hyperfibrinogenemia. The analysis of the ruminal fluid showed compromised microbiota and increased chloride content. The transabdominal ultrasonography demonstrated, in the right ventral region, hypermotile and full small bowel loops and an increase in the volume of the peritoneal fluid. In addition, there was a segment of the small intestine which, in cross-section, showed multiple concentric rings (“onion rings”, “target pattern”, or “bull’s eye”) and adherence to adjacent loops, compatible with intestinal obstruction due to intussusception. Due to the seriousness of the clinical condition and the ultrasound findings, the animal was euthanized and the necropsy revealed focal fibrinous peritonitis and intestinal obstruction due to intussusception in ileum intestinal segments. Discussion: Intussusception has previously been reported in calves, however this is the first report of ultrasound diagnosis of the disease in Brazil. Although the etiology is rarely confirmed, the age group and recent changes in diet (weaning) were predisposing factors. The history, clinical signs, and laboratory tests were similar to those described in cattle with intussusception, however they may be present in other gastrointestinal illnesses. Other authors have also reported that the nonspecificity of the signs and the impossibility of performing transrectal palpation made it difficult to diagnose intestinal obstruction in calves without the use of other diagnostic tools. As it is a non-invasive and accurate technique, ultrasound has been used in ruminants for diagnostic purposes, including intestinal obstructions. In the present case, the main findings are described as the presence of a lesion with the appearance of multiple concentric rings, hypermotile, dilated, and full intestinal loops. The pathological findings were compatible with the ultrasound images and similar to those described by other authors, confirming the diagnosis. The use of ultrasonography as a diagnostic tool in cattle should be expanded, aiming at the early determination of diagnosis and prognosis, to reduce producer costs and animal discomfort. In cases of intussusception, late diagnosis makes treatment unfeasible.